Peran Lapas Kelas 1 Cirebon Dalam Pemberdayaan dan Penanaman Nilai-Nilai Kepada Warga Binaan Pemasyarakatan - Dede Hilda Aulia Fadhilah; Samsudin Samsudin (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2026)
The Correctional System places rehabilitation programs as an instrument for improving inmates’ personal qualities and self-reliance while preparing them for social reintegration. This study examines the implementation of personality and self-reliance development programs, their contribution to empowerment and value internalization, and the constraints affecting their implementation at the Cirebon Class I Correctional Institution. It employs an empirical legal method with a socio-legal approach and a qualitative case study design. Data were collected through observation, semi-structured interviews with correctional officers, instructors, program partners, and inmates, and a review of legislation, activity reports, and relevant literature. The data were analyzed through condensation, coding, categorization, triangulation, and conclusion drawing. The findings indicate that personality development is implemented through religious, civic, educational, artistic, sports, and psychosocial activities. Self-reliance development is conducted through vocational training, handicrafts, garment production, weaving, agriculture, and cultivation programs. These activities contribute to improving skills, discipline, responsibility, cooperation, self-confidence, and readiness for social reintegration. Nevertheless, their implementation is still affected by limited technical personnel, facilities, program continuity, certification, institutional partnerships, and outcome evaluation. The study concludes that rehabilitation should move beyond an activity-based approach toward programs based on individual needs, measurable outcomes, human rights protection, and sustainable post-release support.